Does the experience make a difference? Comparing tourist attitudes pre- and post-visit towards the elephant tourism industry - Emily K. Flower; Georgette Leah Burns; Darryl N. Jones; James McBroom (Annals of Tourism Research Empirical Insights, 2021)
Animal welfare is a significant issue in wildlife tourism and is becoming an important component in tourists' decisions. This study explored the type of tourists who most likely visit different elephant tourism venues and compared tourist attitudes pre-and post-visit. We surveyed 132 tourists at 12 venues in Thailand. We found that participant age was the clearest indicator for the type of venue they were likely to visit and that home location and welfare standards at venues had the greatest effect on attitudes post-visit. Results suggest elephant welfare can be an important factor for some tourists; therefore, efforts should be made to increase public awareness of the issues within elephant tourism venues which could lead to positive attitude and behaviour change.
Keywords: 330; Asian elephant; Animal welfare; Wildlife tourism; Elephant tourism venue; Thailand